2019
DOI: 10.1155/2019/9196729
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Use of Innovative Assistive Technologies among People with Cognitive Impairment and Their Caregivers: A Systematic Review

Abstract: Cognitive impairments (CI), associated with the consequences of Alzheimer’s disease and other dementias, are increasingly prevalent among older adults, leading to deterioration in self-care, mobility, and interpersonal relationships among them. Innovative Assistive Technologies (IAT) such as electronic reminders and surveillance systems are considered as increasingly important tools to facilitate independence among this population and their caregivers. The aim of this study is to synthesise knowledge on facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 53 publications
7
88
1
Order By: Relevance
“…Care workers themselves are often ‘late adopters’ of new technology even though it is used in the care provided to their clients. In a recent review of acceptance and use of innovative assistive technologies among people with cognitive impairment and their caregivers, the results showed how important the communication is for the acceptance and use of digital technology, but also the perceived need for the technology and the expected benefits of its use, as highlighted also by Peek et al . Moreover, in line with previous research how and when the technology was introduced as well as the provision of support before and during the implementation, was highly relevant for acceptance and adherence of the technology.…”
Section: Discussionsupporting
confidence: 72%
“…Care workers themselves are often ‘late adopters’ of new technology even though it is used in the care provided to their clients. In a recent review of acceptance and use of innovative assistive technologies among people with cognitive impairment and their caregivers, the results showed how important the communication is for the acceptance and use of digital technology, but also the perceived need for the technology and the expected benefits of its use, as highlighted also by Peek et al . Moreover, in line with previous research how and when the technology was introduced as well as the provision of support before and during the implementation, was highly relevant for acceptance and adherence of the technology.…”
Section: Discussionsupporting
confidence: 72%
“…28 This is an important aspect and reveals that slow adoption can be linked to more than lack of technological maturity or lack of integration of AT into community health care services. 29 It could also be due to a low understanding of the script of the device; that is, understanding the potential of the technology and how it might be configured to a certain user. 30 Lastly, the participants in our study reported frustrations regarding the limits of the AT and its lack of user interface with citizens' capacities, which points to the complexities of implementing a plan for the integration of AT into the homes of people with MCI/D and into action with the contexts of citizens' lives.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that digital technology can enhance social participation among older people [9], reinforce existing social relationships [10], and mitigate social isolation [11] among older people with dementia. Few studies have explored social participation in relation to technology use, and among those, there is a tendency to focus on novel technological innovations, such as gaming and self-monitoring, which have been limited by high attrition and low uptake in the everyday lives of older people with and without dementia [11,12]. Research based on how older people perceive social participation in a digitalized society found that digital technologies may be perceived as influencing social opportunities, access to services, and a sense of security; however, this research did not include people with dementia [13].…”
Section: Introductionmentioning
confidence: 99%